2012
DOI: 10.1016/j.knee.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparative anatomical study of the human knee and six animal species

Abstract: Purpose Animal models are an indispensable tool for developing and testing new clinical applications regarding the treatment of acute injuries and chronic diseases of the knee joint. Therefore, the purpose of this study was to compare the anatomy of the intra-articular structures of the human knee to species commonly used in large animal research studies. Methods Fresh frozen cow (n=4), sheep (n=3), goat (n=4), dog (n=4), pig (n=5), rabbit (n=5), and human (n=4) cadaveric knees were used. Passive range of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
287
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(308 citation statements)
references
References 28 publications
11
287
0
2
Order By: Relevance
“…The discrepancy in these results has been attributed mainly to the challenges associated with clinical studies of human cohorts, including relatively short followup and lack of outcome measures with sufficient sensitivity to detect sex-specific differences. Instead, the use of large animal models (ie, porcine) has been shown to be a plausible option in the study of ACL injuries and surgical treatments [21,22,34,39,48]. These preclinical models provide researchers with the ability to perform invasive procedures and to measure the relevant outcomes of interest with high accuracy that are challenging, if not impossible, in human trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy in these results has been attributed mainly to the challenges associated with clinical studies of human cohorts, including relatively short followup and lack of outcome measures with sufficient sensitivity to detect sex-specific differences. Instead, the use of large animal models (ie, porcine) has been shown to be a plausible option in the study of ACL injuries and surgical treatments [21,22,34,39,48]. These preclinical models provide researchers with the ability to perform invasive procedures and to measure the relevant outcomes of interest with high accuracy that are challenging, if not impossible, in human trials.…”
Section: Discussionmentioning
confidence: 99%
“…Large animal models including pigs, sheep, goats, dogs, and rabbits have been used as surrogates to study the effects of surgical intervention after ACL injury [7,17,19,20,22,26,44]. Among those, the porcine model has been shown to be the closest to the human based on the size and anatomy of the knee [48], functional dependence on the ACL [10], gait biomechanics [60], and similarity of hematology and wound healing characteristics [15,38,40]. However, it is unknown if the porcine model also could be used to study sex-related phenomena associated with ACL injury.…”
Section: Introductionmentioning
confidence: 99%
“…Magnitudes of neither meniscal resultant loads nor proximity disturbance values seem to explain this trend. Femoral condyle, tibial plateau, and menisci geometries are different between medial and lateral compartments of the ovine stifle (Allen, et al, 1998;Osterhoff, et al, 2011;Proffen, et al, 2012), so perhaps an interaction exists amongst these geometries, alignment and meniscal function that is not obvious from our current data. Numerical models based on subject-specific tissue and osseous geometries, kinematics and kinetics that examine the soft tissue behavior of the cartilage and menisci may be a useful approach to examine these hypothesized interactions more deeply.…”
Section: Discussionmentioning
confidence: 70%
“…It is especially challenging to achieve proficiency in arthroscopic surgery without hands-on repetition [13], and although computer simulators have been available for several years, fluid management, dynamic resistance, and haptic feedback are valuable simulation features afforded to the trainee learning on flesh-and-bone specimens. Training with human cadaveric models is expensive, and porcine knees, with anatomy similar to the human knee, are inexpensive and readily available [10,11,16,21]. Although arthroscopic training using porcine knees is not a novel concept, studies have not shown that the porcine knee is similar enough to the human cadaveric knee for arthroscopic skills assessment [3,10,21].…”
Section: Discussionmentioning
confidence: 99%